Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Sekolah Minggu Buddha Binaan Sangha Theravada Indonesia Se-Kota Tangerang - Ocan Ocan (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
Teachers are one of the important elements in developing the character of students, achieving school goals and improving the quality in the field of education. Teachers are professional educators whose primary task is to educate, teach, guide, direct, train, assess, and evaluate learners on early childhood education pathways of formal education, primary education, and secondary education. One of the semi-formal schools that is closely related to Buddhist religion is the Buddhist Sunday School (SMB). Buddhist Sunday School (SMB) is an educational forum that provides educational activities for students from early childhood to high school. The quality of the Buddhist Sunday School Teacher's Performance will largely determine the quality of the Buddhist Sunday School's educational outcomes. Thismeans that if the Performance of Buddhist Sunday School Teachers is low, it will have an impact on the quality of learning which will have implications for the quality of educational output. Previous surveys showed that the performance of SMB teachers in terms of quantity, quality, time utilization, effectiveness, and efficiency still needs to be improved because it is far from the quality as expected. This st udy aims to find out how motivation and work discipline individually and together can affect the quality of SMB teacher performance. This research was conducted by conducting a survey method and using a qualitative approach. The sample in this study was SMB teachers from 15 Buddhist Sunday Schools in Banten Province totaling 85 respondents. Sample selection is carried out using the purposive sampling type method while the collection is carried out through a questionnaire. The results showed that there was a positive and significant influence between the value of the work motivation variable and the performance of SMB teachers with a coefficient of ry1 = 0.889, a coefficient of determination (ry1) 2 = 0.654 (65.4%) with a regression equation of Y = 56.456 + 0.505X1, There is a positive and significant relationship between the Value of the Work Discipline variable and the value of the SMB teacher performance variable with a coefficient of ry2 = 0.678, a coefficient of determination (ry2) 2 = 0.346 (34.6%) with a regression equation Y = 72.287 + 0.416X 2 , There is a positive and significant relationship between the value of the variable of motivation for achievement and Work Discipline together with the value of the variable performance of SMB teachers with a coefficient of ry12 = 0.847, coefficient of determination (ry12) 2 = 0.718 (71.8%) with regression equation Y = 43.487 + 0.426 X1 + 0.200 X2. This shows that teacher performance can be improved through increasing motivation to excel and Work Discipline which can be done separately or together.